PENERAPAN METODE PROTOTYPE SISTEM INFORMASI PROGRES PROYEK BERBASIS WEB - Sukrianto, Darmanta; Yulianti, Wita; Dwi Oktarina (STMIK KAPUTAMA, 2026)
This research was conducted at PT. Alkamal Consultant, a company engaged in the building construction sector that manages several ongoing projects in Pekanbaru and other regions. The main problem identified is that the process of inputting weekly and monthly project progress data is still carried out manually, where foremen or field supervisors record daily work progress and submit the reports to the admin in paper form every week. Furthermore, the admin processes the data using Word and Excel applications, making the reporting process less effective and efficient. This study aims to develop a web-based project progress information system to facilitate reporting and project information management within the company. The system development method used in this research is the prototype method. The result of this study is a web-based project progress information system that can assist in managing project data more quickly, accurately, and in an integrated manner. The implementation of this system is expected to improve work efficiency and effectiveness compared to the previous manual system.